Subsequent pregnancy outcome after uterine compression suture placement for postpartum hemorrhage. Issue 3 (3rd May 2021) - Subbaiah, Murali; Chaturvedula, Latha; Kubera, Nichanahalli Siddappa; Raj, Ashwini
Abstract: Objective: To evaluate the subsequent obstetrical outcome in women who received a uterine compression suture. Methods: This is a retrospective cohort study of women who received a uterine compression suture for postpartum hemorrhage (PPH) between January 2009 and December 2018 and had a subsequent pregnancy at a tertiary care hospital in India. Women who had PPH but did not receive uterine compression sutures and had a subsequent pregnancy were taken as controls. Results: Sixty‐two women had a subsequent pregnancy after uterine compression suture and were included in this study. There were no significant differences in the subsequent pregnancy outcome between the study and control groups. However, women with a history of uterine compression suture were found to have a higher incidence of dense omental adhesions (15% versus 2.8%; P < 0.001), more intrapartum blood loss (740.5 ± 491.8 ml versus 638.8 ± 194 ml; P = 0.02), and were more likely to need repeat uterine compression suture (6.7% versus 0%; P = 0.004). Conclusion: Women who received uterine compression sutures had similar obstetrical outcomes in their subsequent pregnancy compared with those who did not receive a suture for PPH management. However, they had a higher risk of dense omental adhesions, repeat uterine compression suture application, and intrapartum blood loss. Abstract : Subsequent pregnancy outcome in women who received uterine compression sutures is good. However, they may have more intrapartum blood loss.